Dynamic Socioeconomic Changes and Their Implications on Community Education: A Global Perspective - Hanif, Muh.; Masdub; Rijal, Syamsu (PT. LITERASI SAINS NUSANTARA, 2024)
In the current era of globalization, socioeconomic changes have become increasingly complex and rapid. These changes often result in inequality and disparities that affect access to education. This study aims to analyze the dynamics of social change and its implications on community education from a global perspective. Adopting a qualitative approach through literature review, this research explores community engagement practices in education, focusing on socioeconomic aspects that influence communities. Data were collected from Google Scholar spanning the years 2005-2024. The findings indicate that the dynamics of socioeconomic changes are a complex phenomenon with wide-ranging and diverse impacts on community education worldwide. These changes encompass not only economic aspects such as GDP growth and unemployment rates but also involve social aspects like family structure, cultural values, and political dynamics. Furthermore, socioeconomic changes are influenced by global factors such as international trade, migration, and technological innovation.